2013
DOI: 10.1111/ijsw.12021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of problematic gambling among Danish adolescents

Abstract: This study reports the findings from a national survey on gambling behaviour among Danish primary school children. A questionnaire was administered to 2,223 primary school students ranging in age from 11 to 17 years. The questionnaire contained a gambling screen (SOGS‐RA) and items that measure gambling behaviour, social network and cognitive perceptions. The prevalence of problem gambling was 1.29 per cent, while 4.5 per cent were categorised as at‐risk gamblers. The three most frequently reported reasons for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 51 publications
5
37
0
2
Order By: Relevance
“…In general, adolescent problem gamblers participate in more different gambling activities than non-risk gamblers (Kristiansen and Jensen, 2014), and our data shows adolescent girls also follow this trend.…”
Section: Discussionsupporting
confidence: 51%
“…In general, adolescent problem gamblers participate in more different gambling activities than non-risk gamblers (Kristiansen and Jensen, 2014), and our data shows adolescent girls also follow this trend.…”
Section: Discussionsupporting
confidence: 51%
“…Problem gamblers were also more likely to gamble on the Internet (Olason et al 2011; Kristiansen and Jensen 2014), which could be explained by some characteristics of this gambling mode, such as its accessibility, affordability, convenience and anonymity. In fact, Internet gambling may serve as a good modality for young people engage in gambling activities without age verifications and parental supervision, and therefore may explain the vulnerability of this age group to modern and remote forms of gambling, as some authors had already suggested (e.g., Delfabbro et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, problem gamblers participated in more different gambling activities than non-problem gamblers (Kristiansen and Jensen 2014). The games most played by problem gamblers were slot machines (Forrest and McHale 2012), card games, and sports betting (Skokauskas and Satkeviciute 2007; Lupu and Todirita 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The Loneliness Model (Cacioppo & Hawkley, 2009;Hawkley & Cacioppo, 2010) (Raylu & Oei, 2002), or use gambling as a part of coping with daily stressors, while male problem gamblers are more likely to play in order to win and chase losses (Corney & Davis 2010;Walker, Hinch, & Weighill, 2005). In line with this, a Danish study of a sample of adolescents found that socialisation and boredom were among the only motivations to gamble that were more common among females (Kristiansen & Jensen, 2014). It is relevant to note, though, that an association between gambling and loneliness has also been identified among males (Junttila, Kainulainen, & Saari, 2015 (Wardle et al, 2007).…”
Section: Correlates Of Arpgmentioning
confidence: 95%
“…Nonetheless, a recent national report concluded that gambling among to 17-year-olds in Denmark revealed that 4.7% of males and 2.3% of females were ARPGers, as measured by the SOGS-RA (Kristiansen & Jensen, 2014). In Denmark the age limit on slot machine gambling is 18 years, but the slot machine market is not run by a government-based monopoly (Kristiansen & Jensen, 2014), as is the case in all other Nordic countries.…”
Section: Prevalence Ratesmentioning
confidence: 99%